Perceptions of K-12 teachers on Mobile Augmented Reality in Biology Education: A Descriptive Action Research - Maulion, Raianne Joy; Prudente, Maricar (IJCER (International Journal of Chemistry Education Research), 2025)
This study aims to examine the perceptions of K–12 science teachers regarding the integration of Mobile Augmented Reality (mAR) as a pedagogical tool in Biology education. Specifically, it investigates current mAR usage, its perceived impact on student learning, and the challenges teachers face in its implementation. Using a mixed-method research design, data were collected from 34 teachers through surveys and interviews. Results reveal that only 44.1% of respondents have used mAR in their lessons primarily coming from private schools, while 55.9% have not, primarily due to limited access to devices, unstable internet, and insufficient training. Teachers who employed mAR reported improved student engagement, enhanced visualization of complex concepts, and increased motivation and collaboration. mAR was most used during the engagement and exploration phases, particularly in anatomy and cell biology lessons. Despite challenges in curriculum alignment, technical support, and classroom management, most teachers acknowledge the potential of mAR to enrich Biology education. The study highlights the need for improved infrastructure, targeted professional development, and curriculum-aligned AR content to support wider adoption.